Did Padre Damaso Rape Pia Alba? Reticence, Revelation, and Revolution in José Rizal’s Novels - Hau, Caroline S. (Archīum Ateneo, 2017)
Thisarticle revisits the debate in 2010 among Philippine Daily Inquirer columnists over the question of whether or not, in José Rizal’s novel Noli me tángere, Padre Damaso “raped” Maria Clara’s mother, Pia Alba, a debate inspired by the Reproductive Health (RH) Bill. Thearticle examines how Rizal employs rhetorical strategies of reticence and revelation along with literary onomastics and allusions in his two novels to create meanings and associations that open his novels to multiple, even competing, interpretations. Such ambiguity reveals the artistic, intellectual, and political stakes of interpretation, which involves not only the struggle for understanding and struggle over meaning, but also the struggle to make, unmake, and remake community.Keywords: Rizal • novels • interpretation • crowds and people • community